Analysis of due process in the actions of the Colombian customs authority on imported merchandise. - Duque - Castaño, Yeny Paola; Lukau - Quintero, Claudia Elena; Ceballos - Ramírez, Silvia Liliana (Universidad Francisco de Paula Santander, 2024)
Objective: The purpose of this article is to make an analysis of the due process in the actions of the Colombian customs authority on imported merchandise. Method: the research responds to a qualitative approach, in which a jurisprudential line was carried out through the analysis of sentences issued by the Corte Constitucional and the Consejo de Estado. Results and discussion: It is clear that the Colombian customs authority is competent to carry out prior and subsequent control of the merchandise introduced into the national territory from abroad, however, the process and conditions for each procedure are not clear, since, importers show disagreement with extemporaneous actions, delay of processes, administrative acts issued by the customs entity that violates due process, especially in seizure and confiscation actions. Conclusions: The Sentencia C 441 of 2021 issued by the Corte Constitucional, determined that the process carried out by the customs authority regarding the sanctioning regime is not in accordance with the principle of legal reserve, since in sanctioning matters who has the power to regulate it is The Congreso of the República, therefore, granted a maximum period of until June 20, 2023 to issue the penalty and confiscation of merchandise regime in customs matters, as well as the applicable administrative process.